Effect of current ratio, return on assets and debt to equity ratio on stock price at PT. Tower Bersama Infrastructure Tbk year 2012-2021 - Sairin Sairin; Imam Mahdi (Institute of Computer Science (IOCS), 2023)
The purpose of this study was to determine the effect of Current Ratio, Return on Assets and Debt to Equity Ratio on Stock Prices at PT. Tower Bersama Infrastructure Tbk 2012-2021. The research method is descriptive with a quantitative approach. The research results based on multiple linear regression analysis found the equation Y = -40.507 + -0.266 X1 + 11.105 X2 + 0.011 X3. The results of the t (partial) test for the Current Ratio and Debt to Equity Ratio variables have no effect and are not significant on stock prices, while Return on Assets has a positive and insignificant effect on stock prices. The results of the F test (simultaneous) Current Ratio, Return on Assets and Debt to Equity Ratio have no effect and are not significant on stock prices, with Fcount 3.321 < Ftable 4.35 with a significance of 0.098. And the coefficient of determination (R2) is 0.624 or 62.4%.